2010
DOI: 10.1016/j.ypmed.2009.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of overweight and obesity in a Mediterranean population-based cohort: The Cornellà Health Interview Survey Follow-up Study (CHIS.FU)

Abstract: a b s t r a c t a r t i c l e i n f oObjective. To study the changes in body mass index (BMI) in a population-based cohort and their relationship with sociodemographic variables in a Mediterranean-country.Method. A prospective population-based cohort with 8-year follow-up. The data used derive from the Cornellà-Health-Interview Survey Follow-up (CHIS.FU). 1008 people aged ≥ 20 years (females = 508; males = 500) were interviewed in 1994 and in 2002, providing self-reported weight and height data. The BMI was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“… 30 In Spain and China, there seems to be less risk of obesity among the better-educated. 26 , 31 As education could be a target of prevention strategies, further studies on the risk of developing obesity according to educational level are needed.…”
Section: Discussionmentioning
confidence: 99%
“… 30 In Spain and China, there seems to be less risk of obesity among the better-educated. 26 , 31 As education could be a target of prevention strategies, further studies on the risk of developing obesity according to educational level are needed.…”
Section: Discussionmentioning
confidence: 99%
“…As regard progression from overweight to obesity, we found that the incidence of obesity among overweight participants was slightly higher in women (18.9%) than in men (14.5%), and decreased with advancing age in both genders. In a Spanish study, the incidence of obesity among overweight individuals was twice as high, or greater, in women (29.9%) than in men (13.1%). In a US study, the incidence of obesity among overweight group was also higher in women (16%‐23%) than in men (12%‐13%) across all age groups, and appeared to decline with advancing age in women but not in men.…”
Section: Discussionmentioning
confidence: 92%
“…6,7 To formulate effective strategies for non-communicable disease prevention, it is important to identify groups with high risk of developing obesity using a longitudinal design. Several studies have shown longitudinal data on obesity among adults in Western countries, [8][9][10][11][12] the Middle East, 13 the West Indies 14 and China. 15 In Japan, a large, community-based prospective study presented a 10-year change in overweight and obesity, 16 based on self-reported anthropometric data.…”
Section: Introductionmentioning
confidence: 99%
“…Such gender-related difference was also reported by studies in Croatia (with the 5-year incidence of 8.7% and 20.4% in men and women, respectively)[ 30 ] and Southern Europe (with the incidence being 2 times more in women). [ 31 ] In contrast, the ATTICA study in Greece found the incidence of obesity to be higher in adults men over 18 years old compared to women. It also showed the overall 5-year incidence of obesity and overweight as 8% and 45.4%, respectively.…”
Section: Discussionmentioning
confidence: 96%